PENGARUH LINGKUNGAN KERJA FISIK,LINGKUNGAN KERJA NON FISIK DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. ANDALAS AGRO INDUSTRI(AAI) KABUPATEN PASAMAN BARAT - Afriyeni, Afriyeni; Utami, Kurnia (Ensiklopedia of Journal, 2024)
The Importance of Physical and Non-Physical Work Environments in Improving Employee Performance at PT. Andalas Agro Industry (AAI) West Pasaman Regency is to be able to provide maximum processed palm oil results and good quality production. With a comfortable and conducive work environment, it is hoped that employees will be motivated and able to improve their performance. The purpose of this research is to examine and analyze the influence of the physical and non-physical work environment on motivation and its impact on employee performance. In this research, the population is all employees of PT. Andalas Agro Industry (AAI) West Pasaman Regency, numbering 122 people, the entire population was sampled at 122 people. The research measuring tool uses a Likert scale questionnaire and data analysis uses multiple linear regression tests. The research results show that the Physical Work Environment, Non-Physical Work Environment and Work Motivation have a positive and significant influence on the performance of PT employees. Andalas Agro Industry, West Pasaman Regency.